Isótopos de Carbono em Filitos Carbonosos da Seqüência Metavulcano- Sedimentar Marmeleiro, Sul de Ibaré, Rio Grande do Sul - DE OLIVEIRA, ALESSANDRO SILVA; PULZ, GÊNOVA MARIA; BONGIOLO, EVERTON MARQUES; CALARGE, LIANE MARIA (Pesquisas em Geociências, 2003)
<!– .p text-align: justify; –> Carbon isotope ratios for carbonaceous material in the graphite prospect of Marmeleiro Sequence, southwestern of the Sul-rio-grandense Shield, have been determined. The results are approximately constant with δ13C-values between -27 and -24 per mil. These values suggest that the studied carbonaceous rocks were formed from syngenetic organic detritus, which were converted to graphite during metamorphism. The degree of cristallinity of carbonaceous material has also been investigated. The results of X-ray diffraction [d(002): 3.35 - 3.37 Å] indicate this material cristallinity is intermediate between amorphous carbon and fully ordered graphite.